Aortic Stiffness in L-NAME Treated C57Bl/6 Mice Displays a Shift From Early Endothelial Dysfunction to Late-Term Vascular Smooth Muscle Cell Dysfunction - De Moudt, Sofie; Hendrickx, Jhana O.; Neutel, Cédric; De Munck, Dorien; Leloup, Arthur; De Meyer, Guido R.Y.; Martinet, Wim; Fransen, Paul (Frontiers in Physiology, 2022)
Introduction and Aims. Endothelial dysfunction is recognized as a cardiovascular aging hallmark. Administration of nitric oxide synthase blocker N-Ω-Nitro-L-arginine methyl ester hydrochloride (L-NAME) constitutes a well-known small animal model of cardiovascular aging. Despite extensive phenotypic characterization, the exact aortic function changes in L-NAME treated mice are largely unknown. Therefore, this study presents a longitudinal characterization of the aortic reactivity and biomechanical alterations in L-NAME treated C57Bl/6 mice. Methods and Results. Male C57Bl/6 mice were treated with L-NAME (0.5 mg/mL drinking water) for 1, 2, 4, 8, or 16 weeks. Peripheral blood pressure measurement (tail-cuff) and transthoracic echocardiograms were recorded, showing progressive hypertension after 4 weeks of treatment and progressive cardiac hypertrophy after 8-16 weeks of treatment. Aortic stiffness was measured in vivo as aortic pulse wave velocity (aPWV, ultrasound) and ex vivo as Peterson modulus (Ep). Aortic reactivity and biomechanics were investigated ex vivo in thoracic aortic rings, mounted isometrically or dynamically-stretched in organ bath set-ups. Aortic stiffening was heightened in L-NAME treated mice after all treatment durations, thereby preceding the development of hypertension and cardiac aging. L-NAME treatment doubled the rate of arterial stiffening compared to control mice, and displayed an attenuation of the elevated aortic stiffness at high distending pressure, possibly due to late-term reduction of medial collagen types I, III, and IV content. Remarkably, endothelial dysfunction, measured by acetylcholine concentration-response stimulation in precontracted aortic rings, was only observed after short-term (1-4 week) treatment, followed by restoration of endothelial function which coincided with increased phosphorylation of endothelial nitric oxide synthase (S1177). In the late-disease phase (8-16 weeks), vascular smooth muscle cell (VSMC) disease developed, including increased contribution of voltage-dependent calcium channels (assessed by inhibition with diltiazem), basal VSMC cytoplasmic calcium loading (assessed by removal of extracellular calcium), and heightened intracellular contractile calcium handling (assessed by measurement of sarcoplasmic reticulum-mediated transient contractions). Conclusion. Arterial stiffness precedes peripheral hypertension and cardiac hypertrophy in chronic L-NAME treated C57Bl/6 mice. The underlying aortic disease mechanisms underwent a distinct shift from early endothelial dysfunction to late-term VSMC disease, with continued disease progression.